Front Cover Picture: SBA‐15/POSS‐Imidazolium Hybrid as Catalytic Nanoreactor: the role of the Support in the Stabilization of Palladium Species for C−C Cross Coupling Reactions. (Adv. Synth. Catal. 16/2019). Issue 16 (15th July 2019) - Calabrese, Carla; Campisciano, Vincenzo; Siragusa, Fabiana; Liotta, Leonarda F.; Aprile, Carmela; Gruttadauria, Michelangelo; Giacalone, Francesco
Abstract : Thefront cover picture, provided by Aprile, Gruttadauria, Giacalone and co‐workers, illustrates the inner channels of a inorganic/organic hybrid SBA‐15 containing anchored POSS‐imidazolium bromide moieties as platform for the stabilization of palladium species. The catalyst efficiently works as a nanoreactor for the Heck and Suzuki reactions displaying a high activity and recyclability even at very low loadings. Details of this work can be found in the full paper on pages 3758–3767 (C. Calabrese, V. Campisciano, F. Siragusa, L. F. Liotta, C. Aprile, M. Gruttadauria, F. Giacalone, Adv. Synth. Catal .2019, 361, 3758–3767; DOI:10.1002/adsc.201900350 ).